Traffic Accident Rates by Transportation Mode on the National Road Between Pontianak and Sintang Regency - Betty, Klara Trianisa; Mayuni, Siti; Mukti, Elsa Tri (Fakultas Teknik Universitas Tanjungpura, 2025)
As the capital city of Kalimantan Barat, Pontianak serves as a center for government, trade, industry, and services. This role contributes to high land transportation mobility between Pontianak and Sintang Regency, increasing vehicle volume on the national road connecting the two regions. Consequently, the traffic accident rate on this road segment is relatively high and involves various types of vehicles. This research analyzes the traffic accident rate based on transportation modes to formulate mitigation strategies. The analysis includes categorizing accident characteristics and calculating accident rates based on the incident number and vehicle types. The findings indicate that motorcycles account for the highest number of traffic accidents, whereas buses have the lowest accident rate. The road segment with the highest accident rate is the Tebelian